Metal Biomonitoring Through Arboreal Species in Riparian Ecosystems: Pithecellobium dulce as a Bioindicator Species - Sayuri Hernández-Maravilla; María Luisa Castrejón-Godínez; Efraín Tovar-Sánchez; Hugo Albeiro Saldarriaga-Noreña; Alexis Rodríguez; Marcos Eduardo Rosas-Ramírez; Patricia Mussali-Galante (Plants)
Water pollution by metals is a global environmental problem. In riparian ecosystems, metal pollution generates adverse effects on organisms and reduces water quality. The Cuautla River is of great ecological relevance and an important water supplier. However, it is polluted by multiple wastewater discharges from different origins, with toxic metals being the main pollutants. Therefore, environmental monitoring strategies based on bioindicator species are necessary to evaluate the ecosystem health of riparian ecosystems. Pithecellobium dulce (Roxb.) Benth is a tree species native to Mexico, widely distributed including in riparian ecosystems, and it is also established in contaminated sites. In this study, Cd, Cu, Pb, and Zn concentrations in water and sediment and in leaf and bark of adult P. dulce trees established in six sampling sites along the Cuautla’s riverbed were determined. Likewise, the genotoxic damage derived from metal exposure to leaves was evaluated. The results evidenced the presence of Cd and Pb in water and Cd, Cu, Pb, and Zn in sediment. P. dulce registered high levels of Cu, Pb, and Zn in both leaf and bark, showing higher concentrations in leaf than in bark. In addition, the greater the concentration of Pb in leaves, the greater the genotoxic damage observed, while the concentration of Cu and Zn did not show a relationship with the genotoxic damage in leaves. Overall, Cu and Pb concentrations in leaves enabled us to detect pollution gradients for these metals in water and sediment from the sampling sites. Due to its wide geographic distribution, establishment in polluted sites, and metal absorption capacity, P. dulce can be considered a bioindicator species for environmental health studies in riparian ecosystems contaminated with metals.